2013
DOI: 10.4236/acs.2013.32024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land Use Activities on Spatial and Temporal Variation of Nutrient Deposition in Mwanza Region: Implication to the Atmospheric Loading to the Lake Victoria

Abstract: Increase in population growth and the associated activities have increased the nutrient input to the Lake Victoria through atmosphere and river discharge. Atmospheric input of nutrient is believed to exceed that of river discharge due to relatively higher contribution of water mass to the Lake from atmosphere. However, precipitation characteristics with respect to nutrients have not been well studied to allow qualification and quantification of atmospheric contribution to the Lake Victoria. This study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
(27 reference statements)
4
6
1
Order By: Relevance
“…Mwanza North Bay is under intensive anthropogenic nutrients release attributable to untreated discharges of industrial and domestic wastes and particulate matter direct into the lake via the Mirongo River. Further, the nearshore waters of the Mwanza municipality contain higher nutrient levels due to industrial and vehicle emission (Vuai et al., ). The present study indicated nutrient concentrations of 1,472.20 ± 97.52 μg TN L −1 hr −1 for total nitrogen and 143.69 ± 4.98 PO 4 ‐P L −1 hr −1 for total phosphate concentrations in Mwanza North Bay at the sediment–water interface attributed to the high level of anthropogenic activities in the area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mwanza North Bay is under intensive anthropogenic nutrients release attributable to untreated discharges of industrial and domestic wastes and particulate matter direct into the lake via the Mirongo River. Further, the nearshore waters of the Mwanza municipality contain higher nutrient levels due to industrial and vehicle emission (Vuai et al., ). The present study indicated nutrient concentrations of 1,472.20 ± 97.52 μg TN L −1 hr −1 for total nitrogen and 143.69 ± 4.98 PO 4 ‐P L −1 hr −1 for total phosphate concentrations in Mwanza North Bay at the sediment–water interface attributed to the high level of anthropogenic activities in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Magu Bay is characterized by pollution from agriculture and animal husbandry practices, exhibiting high concentrations of NO 3 ‐N, TN, SRP and NH 4 + ‐N, compared to the pristine site. Previous studies identified agricultural and animal raising as the main contributors of total phosphorus load (Calamari et al., ), phosphorus species and reduced forms of nitrogen species (Vuai et al., ), with net nitrogen releases between 69% and 85% (Zhou et al., ). The nutrients from these sources are carried to the lake as runoff via the Simiyu River, resulting into high levels in the water column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH values and NO 3 − concentrations were similar across study sites of the TSE. This result is likely due to chemical constituents and buffering capacity of lake water, which has also occurred in the Lake Victoria [59]. The minimum pH value at each site ranged from 5.3 to 6.0 (Table S1).…”
Section: Spatial Heterogeneity Of Water Quality In the Tonle Sap Lake-river Ecosystemmentioning
confidence: 94%
“…Concerning the OL, it has been shown that in addition to river discharge, aerial depositions are the main source of nutrient inputs in the lake (e.g., Tamatamah et al, 2005;Kayombo & Jorgensen, 2006). Therefore, a reduction of these inputs would be associated with an integrated approach for the protection of the catchment area, including better soil cover management and improved land use patterns (Okungu & Opango, 2005;Vuai et al, 2013). To adequately protect the watershed, deforestation needs to be halted and forests need to be restored; this constitutes a much greater challenge due to the complexity of the drivers of this phenomenon (Masese et al, 2012;Waiswa et al, 2015).…”
Section: Consequences Of Direct Water Use and Water Supplymentioning
confidence: 99%